2004
DOI: 10.1055/s-2004-818504
|View full text |Cite
|
Sign up to set email alerts
|

Bronchioloalveoläres Karzinom der Lunge assoziiert mit einem hochpositiven pANCA-Titer und dem klinischen Bild einer mikroskopischen Polyangiitis

Abstract: Autoimmune paraneoplastic processes are investigated in detail concerning the Lambert-Eaton-Myasthenic-Syndrome for bronchial carcinomas. For the cutaneous leukocytoclastic vasculitis as a non-ANCA-associated vasculitis the paraneoplastic genesis is described. Litttle is known about ANCA-associated vasculitis as a paraneoplastic autoimmune phenomenon. We present the case of a 62 year old woman referred to our hospital presenting air-space shadows mainly in both upper lobes, skin rash with petechial bleeding an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
5
0
2
Order By: Relevance
“…[22][23][24][25][26][27] Codevelopment of these antibodies and a neoplastic disease is rare, and the link between the 2 processes is not well defined. [22][23][24][25][26][27] Codevelopment of these antibodies and a neoplastic disease is rare, and the link between the 2 processes is not well defined.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24][25][26][27] Codevelopment of these antibodies and a neoplastic disease is rare, and the link between the 2 processes is not well defined. [22][23][24][25][26][27] Codevelopment of these antibodies and a neoplastic disease is rare, and the link between the 2 processes is not well defined.…”
mentioning
confidence: 99%
“…[22][23][24][25][26][27] Codevelopment of these antibodies and a neoplastic disease is rare, and the link between the 2 processes is not well defined. 23,24,28 However, the mechanisms of development of neoplasia-associated vasculitis are complex and the paraneoplastic characteristic of the vasculitis is not constant. It has been suggested that the presence of these antibodies could be related to vasculitis that can develop as an autoimmune paraneoplastic process.…”
mentioning
confidence: 99%
“…Toplam 24 hastada ise solid tümörlerle ilişkili ANCA pozitif vaskülit bildirilmiştir. 4 Baschinsky ve arkadaşları 66 yaşında nonsmoll cell ca (küçük hücreli olmayan akciğer ca) nedeni ile takip edilen ve p-ANCA pozitif pauci-immune crescentic vaskülit nedeni ile takip edilen ve renal yetmezlik nedeni ile ölen bir hasta bildirmişlerdir. 5 Morisako T. ve arkadaşlarının yaptığı çalışmada sol akciğerde kitle görünümü olan ve beraberinde sinüzit hikâyesi olan hastada p-ANCA pozitif olarak saptanmış, bu durum Wegener granülomatozisi'nin eşlik ettiği squamöz hücreli kanser olarak yorumlanmıştır.…”
Section: Discussionunclassified
“…Se ha concedido importancia en la fisiopatogenia de las vasculitis a otros anticuerpos dirigidos contra constituyentes enzimáticos (proteinasa 3, elastasa, mieloperoxidasa, etc) del citoplasma de los neutrófilos (ANCA). De ellos, los p-ANCA con especificidad antimieloperoxidasa se relacionan con la variedad microscópica de la PAN y los c-ANCA dirigidos frente a la proteasa 3 con la enfermedad de Wegener 15 . Los pacientes pueden consultar por síntomas constitucionales tales como malestar general, astenia, pérdida de peso y fiebre.…”
Section: Discussionunclassified